Modelling of the deformation of PTFE-nozzles in a high voltage circuit breaker due to multiple interruptions. (26th February 2016) - Petchanka, A; Reichert, F; Gonzalez, J-J; Freton, P
Abstract: This paper deals with the utilization of an improved model for the PTFE-nozzle deformation caused by the ablation process in the simulation of on-load switching-off processes in high-voltage circuit breakers. In order to describe the plasma's behaviour, a transient axisymmetric model is used, which is based on the @Fluent software. The presented arc model uses mixed formulations for the calculation of the self-induced magnetic field and the radiative heat transfer. The proposed ablation model is based on PTFE evaporation including the nozzle wall deformation. The newly developed approach is used to simulate test series taking into account the accumulated PTFE wall degradation of previous interruptions. The simulation model is validated by the comparison of the simulation results with the measurements. We show the necessity of considering the accumulated nozzle wall degeneration and PTFE evaporation enthalpy in dependence on pressure to yield a good agreement between experiment and simulation.